Fault Surface Rupture Modeling Using Particle Image Velocimetry Analysis of Analog Sandbox Model - Furqan, Terry Alfa; Sapiie, Benyamin; Natawidjaja, Danny Hilman; Widodo, Lilik Eko; Rudyawan, Alfend; Hadiana, Meli (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
This study investigated the correlation between fault kinematics, surficial displacement, and surface rupture geometry patterns between earthquake cycles using particle image velocimetry (PIV) analysis of an analogue sandbox modeling that mimics InSAR observations. The research explored various fault systems, including reverse, normal, and strike-slip faults, through controlled sandbox experiments. The fault surface rupture zone manifests itself due to strain accumulation between two mobile blocks. The displacement magnitude is most pronounced on the surface and is absorbed by the section above the hanging wall or moving block. During fault surface rupture formation, the leading edge of the surface movement consistently extends beyond the anticipated fault surface rupture zone and retreats upon full fault surface rupture development. Subsequently, the distribution of the surface movement is sharply confined by the established fault surface rupture. The key findings of this study underscore the potential of PIV of sandbox modeling for studying fault surface rupture geometry and its development, providing insight into seismic processes. Overall, this work contributes to advancing our knowledge of seismic phenomena and improving strategies for earthquake prediction and mitigation.